Cross-Validation of Paranoid-Depressive Scale and Functional MRI: New Paradigm for Neuroscience Informed Clinical Psychopathology - Stoyanov, Drozdstoy; Kandilarova, Sevdalina; Arabadzhiev, Zlatoslav; Paunova, Rossitsa; Schmidt, André; Borgwardt, Stefan (Frontiers in Psychiatry, 2019)
There is reported a study performed with a novel paradigm aiming at investigation of the translational validity of von Zerssen’s paranoid-depression scale and its fMRI correlates in terms of focus on exploration of the results on the contrast between the Paranoid Specific (DP) blocks and the Depression Specific (DS) blocks. Patients with schizophrenia demonstrated significant activations in a number of regions (right angular gyrus, left posterior cingulate and precuneus, right transverse temporal gyrus) during responses to paranoia versus depression items which differ topologically from those found in patients with major depression (left middle cingulate and right superior temporal gyrus). The direct comparison between the groups, however, did not yield any residual activations after correction.